Teacher Salaries and Racial Inequality in Educational Attainment in the Midcentury South - Cascio, Elizabeth U.; Lewis, Ethan G. (Journal of Labor Economics, 2024)
In the late 1930s, the National Association for the Advancement of Colored People (NAACP) launched a campaign to equalize Black and white teacher salaries in the de jure segregated schools of the American South. We estimate the effect of teacher pay on educational attainment exploiting variation in Black salary gains over time across Southern counties with different Black enrollment shares and across states by whether subsequent policy reinforced or resisted court rulings favorable to the NAACP. Using newly collected county panel data, we find that Black teacher salary gains contributed to the large reductions in racial inequality in school enrollment and grade progression in the South at midcentury.